Functional morphology of the reproductive system and sperm transfer in Stenopus hispidus (Crustacea: Decapoda: Stenopodidea), and their relation to the mating system - Gregati, Rafael Augusto; Fransozo, Vivian; Lopez-Greco, Laura S.; Negreiros-Fransozo, Maria Lucia [UNESP]; Bauer, Raymond (Wiley-Blackwell, 2014)
The morphology of the reproductive system of a stenopodidean decapod is described here for the first time, with an interpretation of the sperm transfer process. Pairs of adults of Stenopus hispidus were maintained under laboratory conditions to observe reproductive cycles. Mating behavior and sperm transfer were video-recorded for analysis. After copulation, the shrimps were anesthetized and dissected to record the shape and location of the gonads, and pleopod morphology was described and illustrated. The reproductive systems (RS), thoracic sterna, and male and female genitalia were observed by scanning electron microscopy. The male reproductive system was restricted to the cephalothorax and was highly reduced compared with that of other decapods. Only the first pair of pleopods may be involved in the sperm transfer process; there was no appendix masculina on the second pair of pleopods as in many other decapods. The ovaries of prespawning females occupied much of the cephalothorax and reached to the 3(rd) abdominal segment. The oviducts were short and simple, without structures for sperm storage. We conclude that the male deposits a simple spermatophoric mass onto the posteroventral surface of the female and fertilization occurs externally as mature oocytes are subsequently spawned. This mode of sperm transfer and egg fertilization is ancestral within the decapod suborder Pleocyemata. As in some other animals, the relatively small size of the testes in S. hispidus may be related to the monogamous mating system, which may minimize selection for a large volume of sperm production.
Keywords: fertilization; insemination; monogamy; ovary; testes